Beban Kerja Terhadap Kinerja Pegawai Pada Kantor Kecamatan Abc - Khasanah, Uswatun; Kardianto Indra Purnomo (Jurnal E-Bis, 2025)
This study is motivated by the importance of government employee performance in supporting the effectiveness of public service delivery at the sub-district level, which requires employees to perform optimally amid variations in workload and increasing service demands from the community. Workload is often perceived as a factor influencing employee performance; however, in practice, this relationship is not always direct. Therefore, this study employed a quantitative approach using a questionnaire as the data collection instrument, which was distributed to 19 employees of the ABC Sub-District Office. Data analysis was conducted using simple linear regression with the assistance of SPSS. The results indicate that workload has no effect on employee performance. These findings suggest that the level of workload experienced by employees does not directly determine the level of performance achieved. The limitation of this study lies in the scope of the research object, which was confined to a single institution. The novelty of this study is reflected in its focus on the ABC Sub-District Office as a sub-district-level government institution with characteristics of workload related to direct public service delivery.